Pemodelan Dampak Perjalanan Bangkitan Terhadap Kecepatan Lalulintas di Kawasan Pertokoan Jalan Urip Sumoharjo Yogyakarta - Perpustakaan UGM, i-lib ([Yogyakarta] : Pusat Studi Energi UGM, 2005)
ABSTRAK Traffic impat can be measured using many indicators including speed changes. Traffic impact assessment of trips generated by activities or new developments in Indonesia is usually carried out using models developed by DPU (1997). The models predict the impact using 2 main indirect variabels, i.e. city size (to cover road user behaviour) and site friction (to cover the rate of activities genereted by the development). These two variables are very rough and sometimes can not predict the traffic impact accurately. Research has been conducted to model the traffic impact of trip generated by shopping areas located on Jalan Urip Sumoharjo Yogyakarta. The data collected consisted of parking configurations, trips generated (measured by the traffic flows coming to and leaving the parking areas), road traffic volumes and speeds, pedestrian flows along the roads, and pedestrian crossing flows. Models were then developed through 3 main steps, i.e. model identification, calibration and validation. It was found that when there were no activities, the free flow speed was 60 km/hour. When there was an increase in the activities along the road (measured by the increase in traffic flows coming to and leaving the parking areas), the road traffic free flow speeds were declining. The traffic speeds were also determined by pedestrian flows. The models for motorcyclists were different from those for passenger cars.